The Influence of Virtual Science Laboratory Design to Increase the Visual Literacy of Prospective Science Teachers - Adisti Yuliastrin; Mery Berlian; Alaniyah Syafaren (Kartika: Jurnal Studi Keislaman, 2026)
Research that uses quasi-experimental methods to reveal the impact of using virtual laboratory media on visual literacy abilities. This research involved two groups, namely an experimental group that was exposed to virtual laboratory media, and a control group that received conventional learning. Both groups underwent a pretest and posttest to measure changes in visual literacy. This research design uses "Nonequivalent Control Group Design" and applies statistical tests such as the Kolmogorov-Smirnov test, Wilcoxon Signed Ranks Test, and Mann-Whitney Test for data analysis. The results showed that the experimental group was superior to the control group, indicating the effectiveness of virtual laboratory media in increasing visual literacy. This indicates that virtual laboratory media can be a valuable tool for modern education, providing a more interactive and interesting learning experience. This media is an alternative and needs to be developed further